Supervision Strategic Management of School Heads In Improving Teacher Performance : Case Study at Cinta Kasih Tzu Chi Middle School, and Vianney Jakarta Middle School - Syahrudin; Achmad Sanusi; Iim Wasliman; Sufyan Sauri (Journal of Islamicate Studies, 2020)
The research entitled Strategic Management Principal Supervision in Improving Teacher Performance is motivated by the low performance of teachers in carrying out their duties and functions. Indications include: incomplete teacher administrative preparation, less interesting and challenging (traditional) learning activities, evaluation of the results of the daily value of the learning process is always measured by a knowledge test, and rarely conduct remedial follow-up programs to improve unfinished scores. The purpose of this study in general was to determine and analyze the strategic management of the head of SMP Cinta Kasih Tzu Chi and SMP Vianney in improving teacher performance. Specifically, the research objectives are to identify and analyze the internal and external environment, plan, implement, evaluate supervision, identify obstacles to the implementation of supervision and provide solutions in overcoming supervision barriers. This research is based on Hunger and Wheelen's (2003) strategic management theory, Peter F. Oliva's (1980) supervision theory, and Bernardin and Rusel's (2002) performance theory. This research uses a qualitative approach. Data collection techniques using interviews, observation, and documentation study. The results of this study generally indicate that the principal's strategic management in improving teacher performance is carried out through internal and external environmental analysis, planning, implementation, evaluation of supervision, identifying barriers to supervision and providing solutions in overcoming supervision barriers. Specifically, the results of this study are shown as follows: 1) Analysis of a strong school environment, especially Human Resources (HR), principals/teachers, and facilities and infrastructure; 2) Supervision planning (teacher administration completeness and time) is still not completing and lacking; 3) Implementation of supervision is not in accordance with procedures; 4) Evaluation of the results of monitoring the supervision of class visits has not been maximal; 5) Barriers to supervision (competence of school principals/teachers need to be improved); and 6) Solutions to overcome obstacles to supervision activities (principals delegate to competent deputy principals / teachers). With the before mentioned conditions, the results of this study are not in accordance with the expectations of the theory/concept of strategic management, supervision, and teacher performance so that strategic supervision of principals with a new innovation of Supervision Coaching Model is needed as the product of this research.